DINAMIKA KONSTITUSIONALISME DAN KRISIS PENEGAKAN HUKUM: REORIENTASI PRINSIP NEGARA HUKUM DI INDONESIA - Kuni Nela Rizki Aszahra; Tomson Situmeang (Fakultas Hukum Universitas Kristen Indonesia, 2026)
This study aims to analyze the root causes of the law enforcement crisis in Indonesia within the framework of constitutional theory and the principle of the rule of law (Rechtsstaat). Although Article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia explicitly stipulates that Indonesia is a state based on the rule of law, in practice, law enforcement is often co-opted by political interests and the pragmatism of power. Employing a normative legal research method and a conceptual approach, this article finds that the law enforcement crisis stems from the deterioration of constitutional morality and weak institutional integrity. The findings indicate that the role of state institutions in maintaining public trust can only be restored through the strengthening of the system of checks and balances and the establishment of absolute judicial independence. This study recommends a reorientation of legal education grounded in constitutional values, as well as the enhancement of external oversight mechanisms over law enforcement institutions.